Synthetic aspects of 1, 4- and 1, 5-benzodiazepines using o-phenylenediamine: a study of past quinquennial. Issue 6 (25th January 2023) - Teli, Sunita; Teli, Pankaj; Soni, Shivani; Sahiba, Nusrat; Agarwal, Shikha
Abstract : This paper presents recent evolutions in the synthetic aspects of 1, 5- and 1, 4-benzodiazepines using o -phenylenediamine as a precursor and provides an up-to-date review of recent findings (2018–2022). Abstract : Benzodiazepines, seven-membered heterocyclic compounds having two nitrogen atoms at different positions, are ruling scaffolds in the area of pharmaceutical industry. They act as cardinal moieties in organic synthesis as well as in medicinal chemistry. Among the different benzodiazepines, 1, 4- and 1, 5-benzodiazepines play a far-reaching role in the field of biological activities such as anticonvulsion, anti-anxiety, sedation, and hypnotics. In the past few decades, researchers have conducted a lot of work on these moieties and developed broad, valuable, and significant approaches for their synthesis. In this review article, we recapitulate the systematic synthetic strategies of 1, 4- and 1, 5-benzodiazepines using o -phenylenediamine as a precursor over the past five years (2018–2022). This article will be helpful for scientists and researchers to examine and explore novel and efficient methods for the synthesis of these biologically active moieties.